Conversation analysis of repair uttered by participant in the erviev video between Emma Watson and Malala Yousafzai - Galang Rizki Ramadhan (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2022)
wt,1/yna, c.1